New frontier set in ideal topological spaces. Issue 5 (4th July 2022) - Al-Swidi, Luay A.; Abdalbaqi, Luma S.; Hasan Hadi, Mustafa
Abstract: Through the concept of local function, we were able to define new boundaries for the set that we called **-frontier. There is a closed and important relationship between this concept and ψ -operator, as has been highlighted in this paper.